The role of the school social worker in addressing behavioral problems - ايفا خرما; ديما رومية (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Our schools are facing many problems, especially behavioral ones, after the Syrian crisis, and appropriate solutions must be found. Our primary goal of our research is to direct attention to the role of the social worker in addressing these problems, where our research dealt with the ingredients of the professional commitment to the school social worker, the factors affecting it, and the strategies that follow it . The school social worker in reducing some behavioral problems: preventive, therapeutic, developmental. So that it can be reachedTo some of the results, including: consolidating the role of social service in schoolThe social worker and providing the appropriate means for him to exercise social service to play his role and solve the problems of students.